Development of a multiplex assay for antibody detection in serum against pathogens affecting ruminants. Issue 3 (29th August 2020) - Hoste, Alexis C. R.; Ruiz, Tamara; Fernández‐Pacheco, Paloma; Jiménez‐Clavero, Miguel Ángel; Djadjovski, Igor; Moreno, Sandra; Brun, Alejandro; Edwards, Thomas A.; Barr, John N.; Rueda, Paloma; Sastre, Patricia
Abstract: Numerous infectious diseases impacting livestock impose an important economic burden and in some cases also represent a threat to humans and are classified as zoonoses. Some zoonotic diseases are transmitted by vectors and, due to complex environmental and socio‐economic factors, the distribution of many of these pathogens is changing, with increasing numbers being found in previously unaffected countries. Here, we developed a multiplex assay, based on a suspension microarray, able to detect specific antibodies to five important pathogens of livestock (three of them zoonotic) that are currently emerging in new geographical locations: Rift Valley fever virus (RVFV), Crimean‐Congo haemorrhagic fever virus (CCHFV), Schmallenberg virus (SBV), Bluetongue virus (BTV) and the bacteria complex Mycobacterium tuberculosis . Using the Luminex platform, polystyrene microspheres were coated with recombinant proteins from each of the five pathogens. The mix of microspheres was used for the simultaneous detection of antibodies against the five corresponding diseases affecting ruminants. The following panel of sera was included in the study: 50 sera from sheep experimentally infected with RVFV, 74 sera from calves and lambs vaccinated with SBV, 26 sera from cattle vaccinated with Mycobacterium bovis, 30 field sera from different species of ruminants infected with CCHFV and 88 calf sera infected with BTV. Finally, to determine its diagnostic specificity 220 field sera from Spanish farms free of the five diseases were assessed. All the sera were classified using commercial ELISAs specific for each disease, used in this study as the reference technique. The results showed the multiplex assay exhibited good performance characteristics with values of sensitivity ranging from 93% to 100% and of specificity ranging from 96% to 99% depending on the pathogen. This new tool allows the simultaneous detection of antibodies against five important pathogens, reducing the volume of sample needed and the time of analysis where these pathogens are usually tested individually.